PENGASUHAN PADA KELUARGA PETANI DAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI JEMPONG BARU KECAMATAN SEKARBELA - Ismayawati Putri; I Wayan Karta; Baik Nilawati Astini; Abdul Kadir Jaelani (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
Parenting applied by parents greatly affects social child's emotions. Conditions of families who have children aged 5-6 years in Jempong Baru Village, Sekarbela District, Mataram City, that children The parents are often left behind by working from morning to evening. The formulation of the problem in this study is how to take care of the family farmer children aged 5-6 years and What are the characteristics of social development emotional farmer children aged 5-6 years. This type of research is qualitative phenomenological, with observations, interviews, analysis of documentation, FGD as The main data collection techniques. The analysis uses qualitative analysis: Data display, data reduction, and data verification. This research found that many arrangements of parenting are applied, more care is done by the mother. Because the father works as the head of the family, but in the father's free time still helps the mother take care of her children, parenting children in this farming family produce children who independent and the communication that is built is also good because they understand the language used by the local community. Thus this thingincluding in democratic family upbringing. Research that carried out must be more in-depth to understand the subject under study, in conducting research must be more intensive so that more data can be obtained and proven results.